Rekomendasi Kebijakan Zero Waste Melalui Pemanfaatan Abu Pembakaran Sampah Residu sebagai Material Konstruksi Berkelanjutan - Tirtha Damayanti; Ni Kadek Sri Ebtha Yuni; I Gede Ryan Kurniawan; Putu Mas Diah Pradnyawati (Jurnal Talenta Sipil, 2026)
The construction sector faces a dual challenge of high carbon emissions and resource depletion, amidst an urgent municipal solid waste crisis in Indonesia. While incineration has been implemented to reduce waste volume, it produces Incineration Bottom Ash and Fly Ash (IBA/IFA) that remains largely underutilized. This study aims to evaluate the potential of Incineration Ash as an eco-friendly construction material and to formulate strategic policy recommendations to support the vision of zero waste and a circular economy. Utilizing a narrative review method of 20 strategic literatures (2015–2025), the research finds that incineration ash possesses superior pozzolanic characteristics, capable of producing construction materials with compressive strengths up to 17 MPa while reducing CO₂ emissions by 14.60% to 22.63%. However, industrial-scale implementation is hindered by a "Regulatory Paradox," where ash is technically proven safe through encapsulation but remains legally classified as hazardous waste (B3) under Government Regulation No. 22/2021. The study formulates three transformative policy recommendations: (1) Reclassifying treated incineration ash as non-hazardous building material post-TCLP testing; (2) Issuing specific national technical standards (SNI) for ash-based materials; and (3) Stimulating market demand through Green Public Procurement. This research concludes that synchronizing environmental regulations with technical infrastructure standards is the key to transforming waste burdens into sustainable construction resources in Indonesia.